Leptin Concentration, Obesity, and Plasma Non-esterified Fatty Acid Levels in Children - Vales-Villamarín, Claudia; Ortega-Senovilla, Henar; Dios, Olaya de; Pérez-Nadador, Iris; Gavela-Pérez, Teresa; Soriano-Guillén, Leandro; Garcés, Carmen (Frontiers in Pediatrics, 2022)
The association between obesity and higher NEFA levels has been established in adults. In contrast, lower NEFA levels have been described in children with obesity although the reason behind this association remains unclear. Leptin, which regulates body weight and plays a role in lipolysis, could be involved in this relationship. We evaluated the influence of leptin in the association between obesity and NEFA concentrations in children, analyzing two cohorts including 684 6-to 8-year-olds and 836 12-to 16-year-old children respectively. After adjusting by leptin, insulin levels remained significantly higher in adolescents with obesity as compared with levels in those without obesity. However, insulin levels showed no differences between prepubertal children with and without obesity. The significantly lower NEFA concentrations observed in 6-to 8-year-old girls with obesity disappeared when comparing NEFA levels between girls with and without obesity after adjusting by leptin. We report an influence of leptin levels on the association between obesity and insulin and NEFA in young children that is not observed in adolescents. Our findings add information about factors that may contribute to explain the lower NEFA levels described in prepubertal children with obesity.